Felipe Sassone (1884-1959). The Spanish journalist who never stopped being Peruvian - Cantavella Blasco, Juan (2011)
There is a little knowledge of writer and journalist Felipe Sassone, who was born in Lima (1884) and died in Madrid (1959), despite his intense literary and journalist life, specially in Spain’s capital city. He embarked very young for Europe, in order to make a success of his work. Quickly, Literature seduces him (novel, theatre, essay, journalism), specially Theatre, writing tons of comedies, as well as directed assemblies and organized companies, where his wife, María Palou, was the leading actress. Memory of both of them has lost in the last fifty years and it is not easy to follow theirs steps in the past, despitetheir acclaimed success.